A Case of Paraneoplastic Peripheral Neuropathy Preceding Plasma Cell Tumor - Güler, Sibel; Acar, Göksemin (Fırat University, 2011)
A Thirty seven year old female patient was evaluated for complaint of walking difficulty more prominent in right leg that increase whenever she climbed up stairs. Patient was previously evaluated for particularly for polyneuropathy etiology. Protein value was found 313 mg/dl in cerebrospinal fluid (CSF) examination. Monoclonal gammopathy was detected in serum and CSF of patient. IgG value in CSF of patient was 39.0 mg/dl. A mass consistent with medullary infiltration was detected in thoraco-lumbar CT. Patient was operated for lytic lesion and pathologic examination of excisional biopsy material was reported as ‘'plasma cell tumor''. As a result of detailed clinical and electrophysiologic evaluations the patient was diagnosed with paraneoplastic sensory motor mixed type polyneuropathy. Consequently, paraneoplastic processes should be considered in etiology of acute and progressive onset polyneuropaties and if possible, detailed studies for etiology should be performed in these patients.

Otuzyedi yaşında kadın hasta sağ ayakta belirgin olan ve merdiven çıkarken artan yürüme güçlüğü ile değerlendirildi. Olgunun polinöropati etyolojisine yönelik olarak ayrıntılı incelemeleri yapıldı. BOS incelemelerinde protein değeri: 313 mg/dl olarak saptandı. Hastanın BOS ve serum incelemelerinde monoklonal gamopati saptandı. Olgunun BOS IgG değeri 39.0 mg/dl idi. Torakolomber BT'de medüller infiltrasyon ile uyumlu kitle saptandı. Hasta litik lezyon nedeniyle opere edildi ve eksizyonel biyopsi materyalinin patolojik değerlendirme sonucu "plazma hücreli tümör " olarak bildirildi. Ayrıntılı elektrofizyolojik ve klinik değerlendirmeler neticesinde paraneoplastik sensorimotor mikst tip polinöropati tanısı aldı. Sonuç olarak akut ve progressif başlangıçlı polinöropatilerin etyolojisinde paraneoplastik süreçler göz önünde bulundurulmalı ve etyolojiye yönelik ayrıntılı incelemeler olanaklar dahilinde mutlaka yapılmalıdır.
Plazma Hücreli Tümöre Öncülük Eden Paraneoplastik Periferik Nöropati Olgusu